Sirah Nabawiyyah Reactualized: Global Mindset in Khulasah Nurul Yaqin Textbook - Habib Al Fattah; Djono Djono; Musa Pelu (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
This study explores the value of the global mindset contained in Khulasah Nurul Yaqin, one of Sirah Nabawiyyah's books and teaching materials popular in pesantren education in Indonesia. Using a qualitative approach, this study collected data from Khulasah Nurul Yaqin's book and analyzed it using three global mindset attributes developed by Project Thunderbird. The validity of the data was ensured through data triangulation by including additional data from various books of the Sirah Nabawiyyah, both classical and contemporary. The findings showed that the three attributes of a global mindset are reflected in the content of Khulasah Nurul Yaqin. First, intellectual capital is reflected by the comprehensive and sharp thinking of the Prophet Muhammad in overcoming various problems, both as a religious leader and head of government. Second, psychological capital is reflected in the Prophet's openness to the diversity around him, his efforts to respect diversity, his openness to opinions, and his confidence to carry out his duties as a Prophet. Lastly, social capital is shown through the Prophet's diplomatic skills and ability to maintain relations with numerous factions inside and outside his government.